2012
DOI: 10.22358/jafs/66059/2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary soyabean, rapeseed and linseed oils on performance, slaughter yield and fatty acid profile of breast meat in turkeys

Abstract: The objective of this study was to determine the physiological effect of supplementing turkey diets with different vegetable oils, i.e. soyabean (S) oil, rapeseed (R) oil and linseed (L) oil, which have different concentrations of polyunsaturated fatty acids (PUFA). The total contents of n-6 PUFA and n-3 PUFA were as follows: diet S, 49.7 and 7.02%, diet R, 33.0 and 7.96%, and diet L, 30.3 and 30.6%; the n-6/n-3 PUFA ratio was 7.3, 4.4 and 1.0, respectively. The experimental materials comprised four groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 15 publications
9
22
0
Order By: Relevance
“…Apparent digestibility of organic matter, crude protein, ether extract and ash was not significantly different (P >0.05) across dietary oil treatments. As observed in the current study, Jankowski et al (2012) found that apparent digestibility of organic matter, ether extract, ash and crude protein was not significantly different in turkeys fed diets supplemented with linseed, rapeseed or soybean oils. In addition, Kavouridou et al (2008) reported that dietary coconut oil, palm oil, olive oil, soybean oil and linseed oil did not influence nitrogen efficiency, but affected fat digestibility.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Apparent digestibility of organic matter, crude protein, ether extract and ash was not significantly different (P >0.05) across dietary oil treatments. As observed in the current study, Jankowski et al (2012) found that apparent digestibility of organic matter, ether extract, ash and crude protein was not significantly different in turkeys fed diets supplemented with linseed, rapeseed or soybean oils. In addition, Kavouridou et al (2008) reported that dietary coconut oil, palm oil, olive oil, soybean oil and linseed oil did not influence nitrogen efficiency, but affected fat digestibility.…”
Section: Resultssupporting
confidence: 79%
“…Thus, increasing mineral levels and different dietary oil may affect intestinal function. Although some investigations have been conducted on the influence of dietary oil sources and Ca requirement on broiler performance and apparent digestibility (Kavouridou et al, 2008;Jankowski et al, 2012), information on the interaction of dietary oil sources and different levels of Ca is limited. Therefore, the objective of this study was to determine the effects of palm oil, soybean oil and linseed oil with three levels of Ca on growth performance, gut morphology and apparent digestibility in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, results of previous studies demonstrated that linseed oil (LO) is a good source of ALA and it can be successfully used for enriching poultry meat with n-3 fatty acids, and thus for obtaining more desirable ratio of n-6 to n-3 PUFA. The latter was clearly confirmed for amount of LO supplementation ranging from 1.25 to 5.5% of diet (Jankowski et al, 2012;Chen et al, 2014).…”
Section: Introductionsupporting
confidence: 54%
“…Linseed oil contains significantly less linoleic acid and significantly more linolenic acid than soybean oil (Kavouridou et al 2008, Jankowski et al 2012. In the present study, diets enriched with linseed oil were characterized by a higher linolenic acid content and more than a three-fold lower n-6/n-3 PUFAs ratio.…”
Section: Discussionmentioning
confidence: 48%